Biodiesel of Groundnut Oil: A Safe Alternate Fuel in the Transport Sector - Chandraju, S.; Prathima, B.K. (Asian Journal of Chemistry, 2016)
Considering pure biodiesel of groundnut oil and its blend up to 10% in particular with heavy duty Karnataka State Road Transport Corporation (KSRTC) vehicles, it is one of the important alternative safe fuels to stabilize green house gas (GHG) emission level in the atmosphere and the results were quite encouraging leading to 22% mileage improvement in groundnut oil ester diesel blend (GOED 10%) compared to 20% in pure groundnut oil ester (GOE). But both have selective improvement compared to diesel. Thus GOED 10% shows 74% improvement and considerable reduction in exhaust emission compared to 73% improvement in pure GOE. The best performance safe fuel compared to HSD is GOED 10% and besides biodiesel of groundnut oil having an agricultural base, it is one of the possible renewable, oxygenated fuel with high calorific value. It strengthens the environmental issues in reducing emission particulates due to low sulphur content of 0.20 in GOE compared to 0.25 in high speed diesel (HSD).